The Mechanisms of Resistin-Like Molecule-β-Mediated Airway Inflammation in Chronic Obstructive Pulmonary Disease via Autophagy - Che L; Xie Z; Chen G; Zhang W; Xia T; Lin J; Luo W; Chen L; Yin W; Cai X; Liu S (Dove Medical Press, 2023)
Li Che,1,2 Zhefan Xie,2,3 Guangshu Chen,4 Wei Zhang,2 Tingting Xia,2,3 Jiaxin Lin,2 Wenzhi Luo,2 Li Chen,2 Wenguang Yin,1 Xingdong Cai,2 Shengming Liu2 1State Key Laboratory of Respiratory Disease, National Clinical Research Center for Respiratory Disease, Guangzhou Institute of Respiratory Health, the First Affiliated Hospital of Guangzhou Medical University, Guangzhou, People's Republic of China; 2Department of Pulmonary and Critical Care Medicine, The First Affiliated Hospital of Jinan University, Guangzhou, People's Republic of China; 3Affiliated Dongguan People's Hospital, Southern Medical University, Donguan, People's Republic of China; 4Department of Endocrinology, Guangzhou Red Cross Hospital, The Affiliated Hospital of Jinan University, Guangzhou, People's Republic of ChinaCorrespondence: Shengming Liu; Xingdong Cai, The First Affiliated Hospital of Jinan University, Guangdong, People's Republic of China, Email tlsm@jnu.edu.cn; cxd19790920@sina.comBackground: The role of irreversible airway inflammatory damage in chronic obstructive pulmonary disease (COPD) progression is evident. Autophagy is an essential process in the cellular material metabolic cycle, and a family of resistant vegetative molecules may be involved in the COPD autophagic process. In this study, we investigated the mechanism of resistin-like molecule β (RELMβ) in COPD smoking-induced autophagy.Methods: Firstly, the expression differences of RELMβ and autophagy markers between COPD and control groups were analyzed in the Gene Expression Omnibus (GEO) datasets and clinical specimens. Secondly, in vitro and in vivo experiments were conducted using immunoblotting, immunofluorescence, immunohistochemistry, and other methods to investigate the mechanism by which RELMβ promotes airway inflammation through autophagy in a cigarette smoke extract-induced 16HBE cell inflammation model and a cigarette smoke-induced COPD-like mouse model. In addition, immunoprecipitation was used to analyze the binding of RELMβ to the membrane protein TLR4.Results: The expression of RELMβ and autophagy genes p62 and LC3B in lung tissue of COPD patients was significantly increased. RELMβ can mediate the activation of autophagy in 16HBE cells, and through autophagy, it increases the expression of inflammatory cytokines in a cigarette smoke extract-induced 16HBE cell inflammation model. RELMβ promotes cigarette smoke-induced COPD-like mouse airway inflammation through autophagy, and RELMβ can mediate signal transduction through the cell membrane receptor TLR4.Conclusion: The RELMβ binds to TLR4 to encourage signal transduction and that RELMβ can promote inflammation in smoky COPD lungs through autophagy.Keywords: autophagy, COPD, airway inflammation, cigarette smoke extract